Survival Strategy In Maintaining The Existence Of The Cak Kiki Sate Stall In Sukarame, Bandar Lampung (Case Study Of The Cak Kiki Satay Stall) - Danu Wijaya; Ni Putu Widhia Rahayu (International Journal of Economics, Business and Innovation Research, 2024)
Cak Kiki Sate Stall in Sukarame Bandar Lampung is an example of a successful culinary SME in the midst of intense business competition. The key to its success lies in its commitment to product quality, friendly service, innovation, consistency, and the provision of adequate facilities. The stall offers regional chicken satay with fresh ingredients and traditional grilling. The service is friendly and courteous, and they continue to innovate with new menus and interesting presentations. Cak Kiki Sate has also been consistent in maintaining the taste of its satay since its inception. Factors that attract customers are friendly service, guaranteed product quality and taste, affordable prices, easily accessible location, and word of mouth. Cak Kiki Sate has proven that with the right strategy, culinary SMEs can compete and thrive in the era of globalization.